Arthritic lesions and congenital fusion in foot bones of Panochthus sp. (Xenarthra, Cingulata) - BARBOSA,FERNANDO HENRIQUE DE S. (2019)
ABSTRACT A set of lesions are re-described and new pathological findings in foot bones of Panochthus sp. (Xenarthra, Cingulata) are presented. The material reexamined in fact presents enthesiophytes instead of osteoartrithis, as previously interpreted. Furthermore, Calcium Pyrophosphate Deposition Disease (CPPD) was observed, a lesion absent in previous report. CPPD also was found in another set of foot bones and it was associated with a congenital fusion of two sesamoids. The material studied were collected in two natural tank deposits, one in Paraíba (material reexamined) and other in Rio Grande do Norte (new pathological findings) State.